ANALISIS KOMITMEN ORGANISASI PEGAWAI TERKAIT GAYA KEPEMIMPINAN TRANSAKSIONAL, TRANSFORMASIONAL, DAN DEMOKRATIS (Studi Kasus di Kecamatan Meurah Dua Kabupaten Pidie Jaya) - Dedi Suyatno; M. Yusuf (IndOmera, 2026)
This article examines employee organizational commitment based on the implementation of transactional, transformational, and democratic leadership styles. The case study was conducted on 41 employees at the Meurah Dua Sub-district Office in Pidie Jaya Regency, using an associative method with a quantitative approach and statistical data analysis through path analysis. The findings indicate that: (1) organizational commitment is directly and indirectly influenced by the implementation of a transactional leadership style by 39.82%. (2) The implementation of a transformational leadership style also has a direct and indirect impact on employee organizational commitment by 53.2%. (3) There are direct and indirect effects of democratic leadership style on organizational commitment by 50.97%. (4) The three factors studied—transactional and democratic leadership styles—are causally interconnected and contribute simultaneously to employee organizational commitment by 85.1%.